School-based deworming programmes: Knowledge and perceptions regarding soil-transmitted helminth infections among schoolteachers in Tamil Nadu, India. - Kumudha Aruldas; Rohan Michael Ramesh; Selvakumar Prasad; Gideon John Israel; Hugo Legge; Judd L Walson; Arianna Rubin Means; Sitara Swarna Rao Ajjampur (PLOS Global Public Health)
In accordance with World Health Organization guidelines, the school-based deworming for soil-transmitted helminths (STH) is being implemented in India since 2015 through teachers on National Deworming Day (NDD). This study aimed to assess teachers' knowledge levels and perception of STH and NDD programmes in southern India using a cross-sectional study design with purposive sampling of teachers involved in the NDD programme. Data from 402 teachers across 221 schools were analysed using STATA 16.0 software. Overall, 37% of the teachers from 52% of schools had attended an NDD training programme. Of a maximum possible score of 32, the knowledge levels were categorised as low (<50%), average (at least 50%), and adequate (70% and above). While 84% of the teachers had an average level of knowledge, only 33% had an adequate level of knowledge. The results showed significant knowledge gaps regarding important aspects of the STH programme including, helminths species being treated, age eligibility of children for treatment, and the name of and side-effects of the deworming tablet distributed. Adequate level of knowledge was more likely among teachers from government schools than those from government-aided/private schools (OR: 3.74; CI: 1.80 - 7.74; p<0.001); those who attended an NDD training programme than those who never attended (OR: 2.69; CI: 1.73 - 4.19; p<0.005); and female teachers compared to male teachers (OR: 1.94; CI: 1.22 - 3.08; p<0.005). A weak but significant positive correlation was observed between knowledge levels and perception (Spearman's rho=0.2075; p=0.002). Teachers from all schools must be encouraged to participate in formal STH training programmes coordinated by the government, and these programmes should be evaluated periodically for effectiveness.